FINDING THE OPTIMAL CONTENT OF COTTON FIBER IN THE MIXTURE (Academicia Globe: Inderscience Research, 2022)
Currently, there is a wide range of factors that affect the development of the country's economy, and one of its specific areas is the textile industry. Solving the problems of this area is one of the factors that have a significant impact on the further development of the economy today and is one of the most pressing issues.